THE CHALANGEOF VOLUNTOURISMFOR BALI TOURISM - Turker, Sidhi (Proceeding SENDI_U, 2017)
The growth of the tourism product development, alternative and special interest developed nowdays for example religious, sport tourism, and is rapidly growing these days is voluntourism.It is a form of tourism product interest the tourist especially from the wealth countries which have the awareness to support quality development in countries that are developing that made sustainable tourism development benefit and a real advantage for the local community.Bali as a growing tourism destination is not paying attention to tourism product opportunities for voluntourism as enriching the tourim product diversification. The object of this article isto answer whether voluntourism-if develop in BALI-can provide the benefits and advantages that are fair for the local community and contribute to the improvement of the quality of sustainable tourism development in the region. To answer the question, raised three problems namely first, how toplan the development of voluntourism as one of the leading alternative tourism in Bali; second, how shall make the voluntourism as a type of tourism product that supports the development of sustainable tourism in Bali;third, how shall the comfort and safety of voluntourists while doing their activity in Bali? The development of voluntourism in Bali should refer to the concept of sustainable tourism development management which must be touched in order that can meet the needs of the future and therefore the concept of development of voluntourism in accordance to the principles of sustainable tourism must be able to make stakeholders of the tourism industry in Bali to see volun-tourism has a promising future and has good prospects moreover role voluntourism organizations are growing rapidly and professionally in organizing programs for voluntourist both short term and longterm. In its approach the development of sustainable tourism, voluntourism, which is based on characterizing the existence of development cooperation from the stakeholders to conduct in-depth studies (from an economic, social, cultural, environmental, etc.) that situational to the emergence of activities that support the development of sustainable tourism The managers of tourist destinations provide education and training to stake holders related based on needs that can accelerate the course of the implementation of the programme of work especially when the very security approach for determining the direction of the area especially when the region rely on tourism as a major industry that support the entire public life not only at the local level but also on a national level. Keywords: voluntourist, voluntourism, alternative tourism, tourism destination, sustainable tourism development.